Source contribution to ozone pollution during June 2021 fire events in Arizona: insights from WRF-Chem-tagged O3 and CO - Y. Guo; Y. Guo; M. A. Mirrezaei; A. Sorooshian; A. Sorooshian; A. F. Arellano; A. F. Arellano (Atmospheric Chemistry and Physics)
This study quantifies wildfire contributions to O3 pollution in Arizona, relative to local and regional emissions. Using WRF-Chem with O3 and CO tags, we analyzed emissions during June 2021, a period of drought, extreme heat, and wildfires. Our results show that background O3 accounted for ∼50 % of total O3, while local anthropogenic emissions contributed 24 %–40 %, consistent with recent estimates for Phoenix. During peak smoke conditions, fire-related O3 ranged from 5 to 23 ppb (5 %–21 % of total O3), averaging 15 ppb (15 %). These estimates were compared with model sensitivity tests excluding fire emissions, which confirmed the spatiotemporal pattern of fire-driven O3, though the model underestimated the magnitude by a factor of 1.4. The results further demonstrate that wildfires exacerbate O3 exceedances over urban areas. Our analysis reveals key differences in O3 sources: Phoenix's O3 was mainly driven by local emissions, while Yuma's was heavily influenced by transboundary transport from California and Mexico. Wildfires not only boosted O3 formation but also altered winds and atmospheric chemistry in Phoenix and downwind areas. O3 increases along the smoke plume resulted from NOX and volatile organic compound (VOC) interactions, with fire-driven O3 forming in NOX-limited zones near the urban interface. Downwind, O3 chemistry shifted, shaped by higher NOX in central Phoenix and more VOCs in suburban and rural areas. Winds weakened and turned westerly near fire-affected areas. This study highlights the value of high-resolution modeling with tagging to disentangle wildfire and regional O3 sources, particularly in arid regions, where extreme heat intensifies O3 pollution, making accurate source attribution essential.